Peripheral Dopamine Directly Acts on Insulin-Sensitive Tissues to Regulate Insulin Signaling and Metabolic Function - Tavares, Gabriela; Martins, Fatima. O.; Melo, Bernardete. F.; Matafome, Paulo; Conde, Silvia. V. (Frontiers in Pharmacology, 2021)
Dopamine is a key regulator of glucose metabolism in the central nervous system. However, dopamine is also present in the periphery and may have direct effects on insulin-sensitive tissues. Dopamine receptor 2 (D2R) agonist bromocriptine is a FDA-approved drug for type 2 diabetes. Herein, we explored the role of peripheral dopamine and its receptors in regulating glucose uptake and metabolism on insulin-sensitive tissues. Peripheral dopamine effect in [3H]2-deoxyglucose uptake in insulin-sensitive tissues was tested in vivo in rats. Direct effects on [3H]2-deoxyglucose uptake, insulin receptor phosphorylation, and regulation of metabolic function were tested ex vivo in the liver, soleus muscle, and white and brown adipose tissues. Bromocriptine and the antagonists domperidone, D2R antagonist, and haloperidol, antagonist of both dopamine receptor 1 (D1R) and D2R, were used to disclose dopamine receptors’ involvement. Peripheral dopamine increases glucose uptake in vivo. Ex vivo, only dopamine increased glucose uptake in the soleus, while bromocriptine increased it in the liver; the effects were reverted by haloperidol and domperidone, respectively. In adipose tissue, domperidone reverted dopamine- and bromocriptine-mediated potentiation of insulin-induced glucose uptake, but in turn increased the insulin receptor, Akt, AMPK, HSL, ACC, and ACL, phosphorylation. In the soleus muscle, AMPK-phosphorylation increased with bromocriptine and dopamine whose effects were suppressed by domperidone and haloperidol. In conclusion, peripheral dopamine stimulates glucose uptake with its receptors being differentially involved in glucose uptake in insulin-sensitive tissues. Dopamine also has a role in lipid metabolism in white adipose tissue. Altogether, these results suggest that peripheral modulation of the dopaminergic system should be further evaluated as a putative therapeutic approach for metabolic disorders.